Clinical and molecular analysis in families with autosomal recessive osteogenesis imperfecta identifies mutations in five genes and suggests genotype-phenotype correlations - Caparrós-Martín, Jose; Valencia, M.; Pulido, V.; Martínez-Glez, V.; Rueda-Arenas, I.; Amr, K.; Farra, C.; Lapunzina, P.; Ruiz-Perez, V.; Temtamy, S.; Aglan, M. (John Wiley & Sons, Inc., 2013)
Autosomal recessive osteogenesis imperfecta (AR-OI) is an inherited condition which in recent years has been shown with increasing genetic and clinical heterogeneity. In this article, we performed clinical assessment and sought mutations in patients from 10 unrelated families with AR-OI, one of whom was presented with the additional features of Bruck syndrome (BS). Pathogenic changes were identified in five different genes: three families had mutations in FKBP10, three in SERPINF1, two in LEPRE1, one in CRTAP, and one in PPIB. With the exception of a FKBP10 mutation in the BS case, all changes are novel. Of note, insertion of an AluYb8 repetitive element was detected in exon 6 of SERPINF1. Since the studied patients had variable manifestations and some distinctive features, genotype/phenotype correlations are suggested. © 2013 Wiley Periodicals, Inc.